Effect of xylanase immobilisation conditions by combination of entrapment and covalent binding on alginate beads - Siti Sabrina, Mohd Sukri; Mimi Sakinah, Abdul Munaim; Wan Zuraida, Wan Kamis; H., Hassan; A. K., Nur Fadzeelah; Sharifah K., Jamaludin (IOP Publishing Ltd, 2020)
The immobilisation of enzymes offer improvement in enzyme stability and characteristics as well as overcome the limitations of free enzyme systems for commercial purposes. In the current study, xylanase was immobilised using a combination technique of entrapment and covalent binding within and onto calcium alginate beads. The sodium alginate and calcium chloride (CaCl2) concentration used for the preparation of alginate beads which is the support matrix for xylanase immobilisation were fixed at 3% (w/v) and 0.3 M, respectively. The effect of immobilisation conditions (agitation rate, enzyme loading, and glutaraldehyde concentration) were studied using One-Factor-At-a-Time (OFAT) approach. The best condition for optimum immobilisation yield (83.93%) was found to be made up of the following parameter combination: agitation rate, 200 rpm; xylanase loading, 200 U; and glutaraldehyde concentration, 12% (w/w). The study shows the immobilisation conditions play a significant role towards the immobilisation yield of xylanase.